Analisis Kualitas Pelayanan Publik Pada Kantor Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan KCP Tabanan - Damayanti, Ni Luh Devi; Wijaya, Komang Adi Sastra; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
BPJS Employment services at KCP Tabanan are based on Law no. 25 of 2009. The BPJS Employment KCP Tabanan office was established in 2015 until now in the implementation of its services there are still unresolved problems. This study aims to determine the quality of public services at the Office of BPJS Ketenagakerjaan KCP Tabanan. This study uses a qualitative research type with a descriptive approach. The technique of determining informants in this study used purposive sampling. The data analysis technique used is an interactive analysis technique which consists of three components, namely data reduction, data presentation, and drawing conclusions. Based on this study using the theory of measurement of public services according to Zeitham1 et al, (1990; 58-60) which consists of 5 indicators, namely direct evidence, reliability, responsiveness, assurance and empathy. Keywords: Public Service, Quality of Public Service, BPJS Employment